Energy intake, household food security and stunting in toddlers at the health center of Molibagu, South Bolaang Mongondow Regency - Punuh, Maureen I.; Akili, Rahayu H.; Mandagi, Chreisye (International Journal Of Community Medicine And Public Health, 2025)
Background: Stunting is a chronic growth problem characterized by an increase in length or height that is not age-appropriate. Key factors contributing to stunting include energy intake and household food security. This study aimed to explore the relationship between energy intake, household food security and stunting in toddlers. Methods: This study is a type of quantitative research with an analytical survey method using a cross sectional design conducted in the work area of the Molibagu Health Center, South Bolaang Mongondow Regency. The sample taken was 121 respondents using accidental sampling technique and met the inclusion and exclusion criteria. Results: The percentage of stunted toddlers was 19.8%, not stunted was 80.2%. The proportion of household food expenditure in the low category was 52.9% and the high category was 47.1%. Energy intake in the deficient category was 38.8% and the sufficient category was 61.2% of toddlers, while protein intake in the deficient category was 20.7% and the sufficient category was 79.3% of toddlers. Analysis related to food security categories showed that families with food security categories amounted to 33.9%, food vulnerable 28.1%, food insufficient 18.2% and food insecure 19.8%. Conclusions: There is a relationship between energy intake and stunting (p=0.008) and there is a relationship between the category of household food security and stunting (p=0.022) in toddlers at the Molibagu Health Center, South Bolaang Mongondow Regency. There is a need to optimize stunting prevention programs and cross-sectoral handling to overcome stunting and wasting in toddlers.